EPR STUDY OF CR3+ DOPING CENTERS IN MG2SIO 4: CR,LI CRYSTALS AND A COMPUTER STRUCTURE SIMULATION - Mineeva R.M.; Kamozin P.N.; Dudnikova V.B.; Urusov V.S.; Gaister A.V.; Zharikov E.V. (My University, 2003)
Powdered samples of Mg2SiO4: Cr and Mg 2SiO4: Cr,Li crystals have been studied using EPR spectroscopy. In chromium-doped forsterite crystals, Cr M31+ and Cr M32+ octahedral centers and tetrahedral Cr4+ centers have been found (all of these centers have been described previously). In chromium- and lithium-codoped forsterite crystals, two previously unknown centers have been found in addition to the CrM31+ and CrM32+ centers. These newly discovered centers have EPR parameters similar to those in lithium-free crystals. The EPR parameters of Cr3+ centers in Mg2SiO4 : Cr, Mg 2SiO4 : Cr, Li, and Mg2SiO 4 : Cr,Al crystals have been analyzed. A computer structure simulation has shown that new centers, which are the chromium-lithium associations CrM31+ -LiM+1 and Cr M32+ -LiM+1, exist in Mg2SiO4 : Cr,Li crystals along with the CrM31+ and CrM32+ centers.